Homecoming: the return of foreign terrorist fighters in South-East Asia - El-Muhammady, Ahmad; Schonveld, Ben (UNDP, 2020)
South-East Asians who went to fight in Iraq and Syria are beginning to return home. Some 800 to 1,400 Indonesians and 100 Malaysians travelled to the Middle East to join the Islamic State (IS) or other groups and a smattering of others from South-East Asian states went too. The number of those who will return home is unknown, and not all will pose a threat. Whatever their experience in the Middle East and whatever their intentions in coming home, all who return—whether or not they face judicial proceedings—will require comprehensive rehabilitation and reintegration to return to society. South-East Asian governments are concerned that returnees may galvanize violent extremism at home. Coordinated responses calibrated to the level of risk and needs of each returnee are necessary. Foreign terrorist fighters (FTF) include not just those involved in active combat but also non-combatants. FTFs include women who went to build the Caliphate declared in 2014 and who may have taken an active role in combat. They include the children who travelled to Syria and Iraq with their parents or those who were born there. Returnees will also include deportees who were detained en route. Many of the highest risk South-East Asian FTFs are being held in Kurdish-controlled camps in northern Syria. In South-East Asia, the FTF phenomenon is primarily a concern for Indonesia and Malaysia. They have previous experience with deradicalization and disengagement programmes, yet little is known about their effectiveness. Indonesia has the largest number of FTFs, including some of the highest risk FTFs, but it has yet to decide how to deal with them. Policies and programming are emerging but are far from comprehensive. In Malaysia there is cross-party agreement to repatriate all Malaysian FTFs as long as they submit to mandatory rehabilitation. Where sufficient evidence exists, individuals will be prosecuted. Returnees will participate in Malaysia’s longstanding deradi- calization programme, which runs in prisons as well as after detention. Those released are subject to supervision orders, counselling and religious education, as well as assistance to facilitate reintegration. Some reintegration responses, particularly in Indonesia, assume that it is possible to replace extremist beliefs with nationalism and “correct” interpretations of Islam. They pay less attention to the complex drivers that led to an individual’s radicalization. This approach is problematic as there is no evidence that “extremist ideas”—perhaps enabled by identity conflicts or group dynamics— by themselves lead people to violence or terrorism. Moreover, government efforts to determine what is legitimate religious belief and practice is fraught with risk. Prisons and prison conditions are central to radicalization as well as to deradicalization and reintegration. If not managed carefully, prisons may allow violent extremist networks to flourish. Some prisons tend to isolate violent extremists from the general population. This approach may harden beliefs; exposure to the general prison population could help challenge such views and increase prospects of successful rehabilitation. Governments need to develop more detailed knowledge of why some people chose to become an FTF in the first place and why they ultimately decided to return to their home countries. Governments need to devote resources to training sufficient staff to assess and monitor returning FTFs and their families. Returnees present varying levels of risk that have to be determined with subtlety and nuance. For example, there are social assumptions that women are low risk, when in fact, women both carry out and drive terrorist attacks. Responses need to be grounded in the law, the protection of human rights and evidence. Many FTFs went to the Middle East to find a like-minded com- munity. They are likely to return to extremist networks if they find themselves isolated or shunned back at home. Many will be wary of them, particularly if they are seen to attract surveillance and intrusion in a community. Working with families, communities and religious leaders is therefore essential. Individuals need to be led away from seeing violence as a solution to their problems and provided with a viable alternative. Policies need to change as situations change, which in itself requires constant and realistic assessments of how well those policies are working.